2023
DOI: 10.1038/s41366-023-01286-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to reduce post-cessation weight gain

Abstract: Background/Objectives Weight gain is a barrier to smoking cessation. Previous interventions targeting weight gain while quitting smoking have largely been unsuccessful. The current study aimed to assess the efficacy of weight stability and weight loss interventions compared to a low-intensity, self-guided bibliotherapy weight management group. Subjects/Methods A randomized controlled trial with 12-month follow-up from 2018 to 2022 was conducted with participants ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Additionally, individuals who enrolled in this trial may have been inherently more motivated to lose or maintain their weight than the general population of individuals quitting smoking. Lastly, only 40%–50% of participants in this study successfully quit smoking; thus, these findings represent a mix of individuals who quit smoking and those who continued to smoke, 26 which could have impacted the findings.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Additionally, individuals who enrolled in this trial may have been inherently more motivated to lose or maintain their weight than the general population of individuals quitting smoking. Lastly, only 40%–50% of participants in this study successfully quit smoking; thus, these findings represent a mix of individuals who quit smoking and those who continued to smoke, 26 which could have impacted the findings.…”
Section: Discussionmentioning
confidence: 88%
“…All methods of the Fit & Quit trial have been described previously, 25 and main outcomes have been reported elsewhere. 26 The goal of the parent study was to investigate the efficacy of a Inclusion criteria focused on recruiting adult cigarette smokers desiring smoking cessation who had a BMI of greater than or equal to 22 kg/m 2 and who were able to participate in study activities (e.g., had email and phone access, could exercise for 10 min). The Loss intervention encouraged all participants to lose at least 5% of their baseline weight to offset expected cessation-related weight gain; thus, the BMI cut-off of 22 kg/m 2 was selected so that even participants with normal weight were able to lose 5% of their baseline The weight management interventions for this study have been described previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of weight gain following smoking cessation is a well-documented concern in scientific research [ 1 ]. Typically, individuals who quit smoking experience an average weight increase ranging from 4.67 to 4.8 kg after 1 year, with more than 10% experiencing a rise exceeding 10 kg [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%